Schmallenberg virus in Culicoides Latreille (Diptera: Ceratopogonidae) populations in France during 2011‐2012 outbreak. Issue 1 (15th August 2017) - Ségard, A.; Gardès, L.; Jacquier, E.; Grillet, C.; Mathieu, B.; Rakotoarivony, I.; Setier‐Rio, M.‐L.; Chavernac, D.; Cêtre‐Sossah, C.; Balenghien, T.; Garros, C.
Summary: Following the emergence of the Schmallenberg virus (SBV) in 2011 in Germany and its rapid spread in Europe, Culicoides (Diptera: Ceratopogonidae) collected through the French surveillance network were analysed in order to record the presence of virus genome into species diversity collected, to assess the minimum infectious rates (MIR) and the virus circulation dynamics in Culicoides populations. Two vector activity periods were selected (2011, August to October, 53 sites and 2012, June to October, 35 sites) corresponding to 704 night collections. A total of 29, 285 individual midges covering at least 50 species were tested either in pools of maximum 50 females or individually (for Culicoides obsoletus / Culicoides scoticus ) using real‐time RT‐PCR. Nine species were found SBV positive ( C. obsoletus, C. scoticus, Culicoides chiopterus, Culicoides dewulfi, Culicoides imicola, Culicoides pulicaris, Culicoides newsteadi, Culicoides lupicaris and Culicoides nubeculosus ) with overall MIR ranging from 0.2% to 4.2%. While the Culicoides nubeculosus laboratory strain is generally considered to have only low vector competence for viruses, interestingly, field‐caught C. nubeculosus specimens were found positive twice for SBV. The first SBV‐positive pool was recorded in August 2011 in north‐eastern France, dating the virus circulation in France 5 months earlier than the first recorded congenital malformations and 2 months earlier than the former recorded date based on retrospective serological data. The MIR were maximum in October 2011, and in July 2012 according to dates of virus arrival in the studied areas. Moreover, our study also showed that virus circulation could be locally intense with infection rate (IR) reaching up to 16% for C. obsoletus / C. scoticus in July 2012 in one site of western France. This retrospective study demonstrates the importance of large‐scale analysis to describe the spatio‐temporal dynamics of virus circulation.